ANALISIS PENANAMAN SIKAP NASIONALISME MELALUI PEMBELAJARAN PKN PADA SISWA KELAS V SD NEGERI1 KOTA LANGSA - Aisyah, Aisyah Khairina; Fitri Hariani Harahap; Addina Maghfirah; Reh Bungana Br Perangin-angin; Sri Yunita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the process of instilling nationalisme attitudes through Citizenship Education (PKn) learning in grade V students at SD Negeri 1 Langsa City. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The subjects of this study consisted of a grade V teacher and 28 students. The results of the study indicate that the instillation of nationalism values ​​has been running optimally. PKn learning does not only focus on cognitive aspects, but also integrates affective and psychomotor approaches that shape students' attitudes and behavior. Teachers utilize various learning methods, such as discussions, inspirational stories, and visual media to foster a sense of national spirit. In addition, supporting activities such as flag ceremonies, nationalism-themed competitions, and educational visits also strengthen students' understanding of national values. Active involvement of students in the learning process and support from schools and parents are important factors in the success of instilling nationalism attitudes in students. This study recommends that learning strategies like this continue to be developed sustainably to form a young generation who love their country.